2016
DOI: 10.1038/srep37079
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthetic gene cluster for the cyanogenic glucoside dhurrin in Sorghum bicolor contains its co-expressed vacuolar MATE transporter

Abstract: Genomic gene clusters for the biosynthesis of chemical defence compounds are increasingly identified in plant genomes. We previously reported the independent evolution of biosynthetic gene clusters for cyanogenic glucoside biosynthesis in three plant lineages. Here we report that the gene cluster for the cyanogenic glucoside dhurrin in Sorghum bicolor additionally contains a gene, SbMATE2, encoding a transporter of the multidrug and toxic compound extrusion (MATE) family, which is co-expressed with the biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 47 publications
0
67
0
1
Order By: Relevance
“…This result is significant, given the recent interest in breeding vegetables for high-nutrient density [ 11 ]. Also in this clade is SbMATE2 from sorghum, which transports toxic hydroxynitrile glucosides (e.g., dhurrin) to the vacuole of cells in diverse tissues of the plant [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result is significant, given the recent interest in breeding vegetables for high-nutrient density [ 11 ]. Also in this clade is SbMATE2 from sorghum, which transports toxic hydroxynitrile glucosides (e.g., dhurrin) to the vacuole of cells in diverse tissues of the plant [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the L. japonicus genome revealed that the biosynthetic genes for linamarin and lotaustralin are organized in a biosynthetic gene cluster and helped identify CYP736A2 as responsible for the second enzymatic step (Takos et al, 2011). We also reported the existence of biosynthetic gene clusters for cyanogenic glucosides in the genomes of cassava and sorghum, of which the latter was shown to contain additionally a vacuolar MATE-type transporter for dhurrin (Darbani et al, 2016). A gene cluster in barley (Hordeum vulgare) contains the CYP79 and CYP71 genes that encode the enzymes for the production of five leucine-derived α-, β-, and γ-hydroxynitrile glucosides, including the cyanogenic glucoside epiheterodendrin (Knoch, Motawie, Olsen, Møller, & Lyngkjaer, 2016).…”
Section: Introductionmentioning
confidence: 86%
“…For example, a transporter from the multidrug and toxic compound extrusion (MATE) family identified within the monoterpene indole alkaloid (MIA) gene cluster is involved in translocation of the intermediates of the MIA pathway (Kellner et al ., ). In sorghum, the vascular membrane protein SbMATE2 is co‐located with the cluster genes and able to transport dhurrin (Darbani et al ., ). Based on the fact that plants are likely to need transporters to translocate specialized metabolites to the right locations, identification and characterization of the transporters involved in counteracting the toxicity or unpleasant flavors conferred by the defensive compounds could provide key knowledge for improving crop quality and also simplify the procedure of metabolic engineering of natural plant products by pumping target compounds out of plant cells or microbes (Xiao and Zhong, ).…”
Section: Efficient Mining Approaches For Plant Metabolic Pathway Studiesmentioning
confidence: 97%